Aplicación móvil Autocut: Una alternativa de movilidad compartida en el Centro Universitario de Tonalá, Universidad de Guadalajara-México. - Asprilla Lara, Yefer; Dávila Velázquez, José Ramón; Reyes Aguilar, Humberto; García De Quevedo, Fernando; Guerrero de León, Aida Alejandra; Villanueva Álvarez, Graciela (Tecnogestión: Una mirada al ambiente, 2019)
Urban mobility is becoming is keystone in in large metropolitan areas. Hence, information technolo-gy offers a large variety of tools to promote a safe, sustainable and inclusive mobility through carpoo-ling or car sharing in accordance to UN Habitat III urban agenda. The work at hand focus in the design process and development of a mobile app entitled “AutoCUT”, that provides a technological framework for car sharing or carpooling among the student and faculty community at Centro Uni-versitario Tonalá of Universidad de Guadalajara. The methodology included the app development using Android® operating system and literature review for both code programing and carpooling trends. The result is a safe (i.e., student and facul-ty are validated trough registrar’s office records), free and real-time app that offers basic information of all users (i.e., drivers and passengers), routes, seats available and departing schedules. All these attributes converge to produce a safe alternative for carpooling.